No Clear Differences between Organic or Conventional Pig Farms in the Genetic Diversity or Virulence of Campylobacter coli Isolates - Denis, Martine; Nagard, Bérengère; Rose, Valérie; Bourgoin, Kévin; Cutimbo, Mélina; Kerouanton, Annaëlle (Frontiers in Microbiology, 2017)
To evaluate the impact of pig farm management on the genetic diversity and on the virulence of Campylobacter coli, we characterized isolates from 19 organic pig farms (62 isolates) and from 24 conventional pig farms (58 isolates). The 120 C. coli isolates were typed using pulsed field gel electrophoresis (PFGE) and multilocus sequence typing (MLST) and the presence of nine virulence genes was screened using real-time PCR. The capacity of adhesion and invasion of 61 isolates (32 from organic and 29 from conventional farms) were then tested on human intestinal Caco-2 cells. A total of 59 PFGE types and of 50 sequence types (STs) were identified. Twelve PFGE types and nine STs, accounting for 34% and 41.6% of the isolates, respectively, were common between the two production systems with ST854 dominating (18.3% of the isolates). Twenty-nine PFGE types and 25 STs were only found in isolates from organic farms, and 18 PFGE types and 16 STs from conventional farms. No significant differences were found in diversity despite the differences in rearing systems, except at the locus level for the glnA, gltA, and uncA genes. All isolates, regardless of their origin, carried the ceuE, iam, ciaB and flaA genes and more than 95% of the isolates carried the cadF and cdtABC genes. No significant differences were found in pathogenicity between the two farming systems. The pathogenicity of the C. coli isolates was low compared to C. jejuni control strains tested. The plasmid gene virb11 was detected in only 13 isolates from organic farms; these isolates showed greater invasion capacity than those without this gene. Our study indicates that pig farm management does not significantly affect the diversity and the virulence of Campylobacter coli isolated from pigs. The common genotypes between conventional and organic farms may indicate that some genotypes are adapted to pigs.